Identifying Criteria for a Successful Marriage: A Grounded Theory Study - Nikooy, Maryam; Asgharirad , Ali Akbar; Najari Forushani , Samaneh; Mehregan , Mohammad (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aims to identify the criteria for a successful marriage through a qualitative approach using grounded theory methodology.Methods: This qualitative study employed grounded theory with a systematic approach. Participants included 12 married individuals from Iran, selected through purposive sampling. Data were collected via semi-structured interviews, analyzed using open, axial, and selective coding following Strauss and Corbin’s method. Lincoln and Guba’s criteria for trustworthiness were applied to ensure the reliability of findings.Findings: The study identified five paradigms: central factors, causal factors, contextual factors, facilitating factors, and outcomes, encompassing 11 main categories, 21 subcategories, and 45 initial codes. The central category of "couple interactions" included emotional regulation, mutual understanding, intimacy, commitment, and satisfaction as key indicators of a successful marriage. Causal factors included initial attraction, emotional maturity, and family interactions during courtship, while facilitating factors highlighted family support. Contextual factors such as economic, cultural, familial, and individual aspects were also significant.Conclusion: The findings emphasize that successful marriages are influenced by a combination of individual, relational, and contextual factors. Practical applications include incorporating these insights into premarital counseling, marital therapy, and educational programs to promote emotional well-being, mutual understanding, and satisfaction in marital relationships.